Predictors of academic integrity in undergraduate and graduate-entry masters occupational therapy students - Ted Brown; Stephen Isbel; Alexandra Logan; Jamie Etherington (SAGE Publishing, 2020)
Background: Academic integrity is viewed as honest and responsible scholarship and the moral code of academia. Reported incidences of academic dishonesty among health professional students are widespread and may be an indicator of future unprofessional behaviour in the workplace. Aim: This study investigated the potential predictors of academic integrity in undergraduate and graduate-entry masters occupational therapy students. Method: Occupational therapy students from five universities ( n  = 701 participants; 609 undergraduates; 92 graduate-entry masters) were recruited. Data were collected via a two-part self-report questionnaire that included six standardised scales: Academic Dishonesty Scale; Academic Dishonesty in the Classroom Setting Scale; Academic Dishonesty in the Clinical/Practice Education Setting Scale; Moral Development Scale for Professionals; Academic Dishonesty Tendency Scale; and Perceived Academic Sources of Stress. Data analysis involved multi-linear regression analyses with bootstrapping. Result: Significant predictors of academic integrity in occupational therapy students included age, gender, grade point average, public meaning, moral practice, general tendency towards cheating, tendency towards dishonesty in the conduct and reporting of research findings, tendency towards not providing appropriate references and acknowledgements and pressures to perform well academically. Conclusion: These findings will assist educators in identifying vulnerable students potentially prone to academic integrity infringements and implementing proactive strategies with them. Further studies are recommended to explore further predictors of students' academic integrity.